Design and manufacturing of a hybrid flax/carbon fiber composite bicycle frame - Amiri, A.; Krosbakken, T.; Schoen, W.; Theisen, D.; Ulven, C. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Carbon fiber composite frames were first used in Tour de France in 1986. With recent growth in research and development of composite frames, carbon fiber composites have become more popular in bicycle industry where lightweight and high stiffness are of upmost importance. Unfortunately, carbon fiber is expensive and has low impact toughness. One method of overcoming this shortcoming is to hybridize carbon fiber with natural fibers such as flax. The benefit of using hybrid composites is that the advantages of one type of fiber can overcome the disadvantages of the other type of fiber. As a result, a balance in cost, performance, and sustainability could be achieved through proper composite material design. In this study, carbon fiber was hybridized with flax fiber in an effort to manufacture a bicycle frame with the high-performance characteristics of carbon fiber and low cost and renewability of flax fiber. In addition, vibration damping properties of flax fiber will result in a more comfortable ride. The results of mechanical tests of the frame material revealed that the manufactured frame possess similar or higher stiffness and strength as commercially available carbon, titanium, and aluminum frames while exhibiting superior vibration damping properties. All these were achieved with a lower cost compared to carbon composite frames while maintaining 40% biocontent.